Endoscopic transorbital eyelid approach for the removal of an extraconal cavernous venous malformation: Case report - Fabozzi, Gianluca Lorenzo; d’Avella, Elena; Burroni, Matias; Romano, Antonio; Cavallo, Luigi Maria; Solari, Domenico (Frontiers in Surgery, 2022)
Cavernous venous malformations (CVMs) are one of the most common benign primary orbital lesions in adults and the second most frequent cause of unilateral proptosis. Extraconal location is extremely rare, representing a favorable condition as compared to intraconal, as lesions at this level often adhere to orbital muscles and optic nerve. Herein, we report the case of a 50-year-old patient, who came to our attention because of progressive painless right axial proptosis. Magnetic resonance images were consistent with an extraconal CVM, occupying the superior temporal compartment of the orbit. Successful removal of the lesion was achieved through an endoscopic transorbital eyelid approach. The present case confirms the safety and efficacy of the endoscopic transorbital eyelid approach.